Phytochemical analysis of secondary metabolite compounds of Pandanwangi leaf extract (Pandanus amaryllifolius) - Sa'adah, Siti Malihatus; Putri, Fensy Rania; Ibtisam, Afina Anjani; Arrohmah, Robiatush Sholichah; Fitriyah, Fitriyah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
The majority of people use pandan as a dye, food fragrance, and natural medicine because it contains secondary metabolites such as alkaloids, saponins, and phenolics. Therefore, this research aims to explore the secondary metabolites of Pandanus amaryllifolius using qualitative and quantitative methods. The research begins by taking samples of pandan leaves, which are then extracted and tested qualitatively and quantitatively. The qualitative test results showed that pandan leaf extract contained flavonoids, polyphenols, and tannins. In the quantitative test of pandan leaf phenolic compounds using a UV-Vis spectrometer with gallic acid concentrations of 80 ppm, 100 ppm, 120 ppm, and 140 ppm, Based on the quantitative test, the total phenolic content of pandan extract is 114 mg/L.